Epidemiology of tuberculosis in Morocco: diagnosis, treatment, quality of life, and associated factors - El Bahi, Youssef; Loulidi, Soukaina; Loukid, Mohamed; Rkha, Samia (International Journal of Public Health Science (IJPHS), 2025)
Tuberculosis remains a major public health challenge worldwide, despite significant advances in treatment and prevention. In Morocco, 30,000 cases of tuberculosis are recorded each year. In the Marrakech-Safi region, the incidence reaches 50 cases per 100,000 inhabitants. The aim of this research was to assess the effectiveness of current diagnostic and treatment, and to measure the impact of tuberculosis on patients' quality of life. A cross sectional study was carried out on a sample of 480 tuberculosis patients. The results showed that low education levels (53.86%) and high unemployment (40.8%) were prevalent. More than 51% of patients do not have health insurance. High housing density was correlated with increased prevalence, and diabetes was frequent (40.19%). 27.50% used medicinal plants, and 13.11% interrupted medication due to long treatment duration. Males were more symptom-free (p<0.000). Males had more severe symptoms than females such as sputum (163 vs. 58 cases), weight loss (224 vs. 131 cases), cough (184 vs. 86 cases), and hemoptysis (70 vs. 27 cases). Urban residents showed significant differences in tuberculosis types (p = 0.034). Occupation and prior treatment influenced tuberculosis distribution and extrapulmonary tuberculosis prevalence (p = 0.000). 21.46% were permanently affected in their social life. Higher education level and non-smoking was linked to better health (p = 0.016; p = 0.002). These results contribute to a better management of diagnostic, treatment, and prevention strategies adapted to tuberculosis patients by strengthen health education and promote rapid access to specialist care.